Some Aspects of the Ecology of Elaeidobius Kamerunicus Faust, The Pollinating Weevil of Oil Palm, With Emphasis on Developing Sampling Techniques - Chiu, Sheng Bin (1984)
Some aspects of the ecology of the pollinating weevil of oil palm, Elaeidobius kamerunicus Faust - an exotic insect to Malaysia imported from Cameroon, West Africa, three years ago - were studied in 1983 and 1984. In particular, sampling techniques for estimating the weevil population were developed and the effect of rat predation on the immature weevils was studied. In the course of these studies, certain aspects of the weevil's behaviour and activity were investigated. Field studies concerning the ecology of the weevil requires a satisfactory method for estimating the weevil population. Three sampling methods were compared: petridish traps set on receptive female inflorescences, sticky traps incorporating anthesising male flowers as bait, and sampling the weevil-covered spikelets of the anthesising male inflorescence. The last method was found to be superior it was more reliable and the data could be converted to an absolute estimate. To be reliable, the method must consider the time of sampling, stage of anthesis of the male inflorescence, and position of spikelet on the male inflorescence. Taking samples after 5 pm, separating the anthesising male inflorescences into three stages, and stratified sampling from six sections of the male inflorescence were found to be optimal for a reliable estimation.